Assessing The Effectiveness Of The 'Read With Miley' Program In Developing Reading Skills Among Chinese Children Teachers' Perspective/ تقييم فعالية برنامج 'اقرأ مع مايلي' في تنمية مهارة القراءة لدى الأطفال الصينيين من منظور المعلمين - Sedira, Amel; Abdullah, Nurazzelena; Che Haron, Sueraya; Mamat, Ariffin; Nawi, Amani; Yusup, Agung (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
With the growing interest in teaching Arabic to non-native, Chinese-speaking children—particularly in contexts related to religious and cultural identity—there is a critical need to evaluate innovative educational programs that address linguistic and cultural challenges. This study examines the effectiveness of the